(untitled) (Indian Journal of Animal Production and Management, 2017)
Frieswal (HF x Sahiwal) are the important crossbred cattle population in India for milk production. An investigation was carried out with farmers of U.S. Nagar district of Uttarakhand on Frieswal heifers/ cows during Nov. 2010 to Feb. 2016 to study the effect of various non-genetic factors (blocks, herd size, land holding, education level of farmers, caretakers of herd, marketable milk surplus, season/ year of birth/ calving) on age at first service, age at first conception, no. of services required for first conception, age at first calving, first service period and first calving interval using least-squares analysis of variance. The overall least-squares means for these traits were 840.7±57.9 days, 906.6±64.9 days, 1.75±0.29, 1103.2±80.6 days, 142.1±4.2 days and 520.1±47.4 days based on 569, 539, 538, 337, 163 and 88 observations, respectively. These traits were significantly affected by varying non-genetic factors. Information on this aspect is useful in implementing any large scale field based animal breeding program with respect to crossbred cattle in general and Frieswal cattle in particular.